MEDITASI SEBAGAI MIND BODY MEDICINE - I Komang Yuni Arta (Sanjiwani: Jurnal Filsafat, 2019)
Humans are one of the tangible proofs of existence in the universe whose life holds many mysteries that are very interesting objects of curiosity. Human life which is a perfect relation of two dimensions of life, is called sekala or material world and niskala or transcendent world becomes a space of inquiry to create a balanced life physically and spiritually. The many problems experienced by humans make meditation a very powerful technique in understanding human life materially and spiritually. In various scientific studies it has been found that meditation can help a person to revitalize his life both biologically and mentally. This practice becomes moderate between a person’s mind and body, which when a person’s mind is in a positive or negative state, will directly affect its biological aspects. Meditation in this case acts as a mind body medicine that creates a placebo effect that is able to provide a variety of positive effects on a person’s life through mechanisms that will change his perception and beliefs. Therefore, meditation as mind body medicine is a very important practice to be carried out to create a healthy mind, mental and physical for a healthy and harmonious life.